INTERFACE MANAGEMENT PADA INTER-PUBLIC INFRASTRUCTURES SYSTEM RUANG MILIK JALAN - Bukit, Ipak Neneng Mardiah; Marzuki, Puti Farida; Tamin, Rizal Zainuddin; Wiratmadja, Iwan Inrawan (JURNAL TEKNIK SIPIL, 2023)
Abstract: The public right of way is a place for utility infrastructure facilities such as clean water pipes, electicity cable, and telecommunication fiber optic cable involving multi-independent stakeholders. Indonesian cities in general have no utility ducting system along its roads, thus utility facilities are placed in and adjacent to the public right of way as overhead and underground line. Stakeholders activities during operational and maintenance phase of the existing road potentially damage nearby infrastructures, causing repeated repair all over the year, and lead to service disturbance, traffic disruption, and users complaint due to lack of communication skill and lack of stakeholders coordination. This paper describes inter-public infrastructure management using soft system based interface management to reduce the effect of poor communication and coordination amongst stakeholders. Managing interface is conducted within four stages of concept and procedure, namely: interface identification, interface simplification, interface priority, and interface matching. The result of discussion concluded that the road authority needs to pay more attention to user/community complaint toward service disturbance by improving coordination and communication system among stakeholders in order to reduce infrastructure damage.Keywords : coordination, communication, interface management, public infrastructures, soft system.Abstrak: Ruang milik jalan (rumija) menjadi tempat infrastruktur utilitas seperti air bersih, kelistrikan, dan telekomunikasi yang melibatkan multi-stakeholders yang berasal dari organisasi-organisasi yang independen. Kota-kota di Indonesia pada umumnya belum memiliki fasilitas bersama untuk infrastruktur utilitas sehingga diletakkan di sepanjang jalan baik sebagai saluran udara maupun saluran bawah tanah. Kegiatan pekerjaan utilitas terjadi sepanjang masa operasional dan pemeliharaan jalan berpotensi merusak infrastruktur lain yang ada didekatnya, menyebabkan perbaikan terus menerus sepanjang tahun, dan mengakibatkan gangguan pelayanan, kemacetan lalulintas, dan keluhan masyarakat akibat dari lemahnya komunikasi dan koordinasi antar stakeholders. Paper ini bertujuan untuk mendeskripsikan pengelolaan inter-public infrastructure system rumija dengan interface management system berbasis soft system thinking sehingga dampak dari lemahnya komunikasi dan koordinasi dalam interfaces dapat dikurangi. Pengelolaan interface dilakukan dengan empat langkah konsep dan prosedur, yaitu; identifikasi interface, penyederhanaan interface, prioritas interface, dan interface matching. Hasil pembahasan menyimpulkan masalah interface yang harus diberi perhatian lebih yaitu terjadinya keluhan masyarakat terhadap gangguan pelayanan dengan memperbaiki sistem koordinasi dan komunikasi antar stakeholders sehingga kerusakan infrastruktur dapat dikurangi.Kata kunci : interface management, infrastruktur publik, komunikasi, koordinasi, soft system.